The Determinant Factors Analysis of Indonesian Students’ Environmental Awareness in PISA 2015 (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
This research intended to reveal the determinant factors which could explain Indonesian students’ environmental awareness based on the 2015 PISA; also, to find out the influence of Science Proficiency to Indonesian students’ environmental awareness based on PISA 2015. The data were obtained from the 2015 PISA database in which there were 6513 Indonesian students participated in the survey. This research employed the Path Analysis continued to the Structural Equation Modelling (SEM) employing the LISREL 8.30. The research results indicated that the environmental awareness of 15-old Indonesian students directly influenced positively by: (1) students’ enjoyment of learning science equal to 0.41; (2) students’ self-efficacy in science equal to 0.16 (3) students’ instrumental motivation equal to 0.15 ; (4) Inquiry-based instruction in science lesson equal to 0.14; (5) students’ science proficiency equal to 0.11; and (6) students’ epistemic belief equal to 0.04. The higher the socio-economic status of the students, the lower the environmental awareness. A respectable correlation of 0,5 was obtained from the relationship between those 6 variables and environmental awareness.